Lower body positive pressure treadmill gait training for neurological patients: a systematic review - Sattam M. Almutairi (Bulletin of Faculty of Physical Therapy, 2023)
Abstract Background Among various body weight-supported locomotor training methods for neurological patients, some studies have recognized the lower body positive pressure (LBPP) treadmill as superior for gait training in neurological patients. The aim of this study is to explore the clinical use and efficacy of LBPP treadmill gait training in neurological patients. Methods A systematic review was performed following PRISMA guidelines. The inclusion criteria were studies published in English using LBPP with neurological patients were included from the database's inception to March 2023 to avoid misinterpretation of translation. The search was conducted in multiple databases, including Google Scholar, PubMed, Scopus, PEDro, and the Cochrane Database. To improve accuracy and comprehensiveness, studies mentioned in the main articles were also evaluated. Results The search identified 16 articles that use LBPP with neurological patients. Only a few randomized control studies on the use of LBPP after stroke have been reported. For neurological rehabilitation, LBPP treadmill gait training is safe and feasible. Current research suggests that using the LBPP treadmill in conjunction with traditional rehabilitation treatment has a successively beneficial impact on motor function, particularly in patients with subacute to chronic stroke and Parkinson’s disease. There are no studies that compare the LBPP to the body weight supported treadmill (BWST). Furthermore, to the best of our knowledge, the LBPP treadmill has not yet been evaluated on for its effectiveness in treating traumatic brain injury (TBI) or spinal cord injury (SCI). Conclusion There was insufficient evidence to support the claim that LBPP is effective and superior to other gait training methods. Larger randomized control studies with sufficient sample sizes are needed to better understand the potential effects of the LBPP treadmill intervention on the functional performance of people with neurological disorders.